How effective is antenatal care in preparing mothers for newborn care? An exploratory survey of lactating women in a rural Nigerian district - Adebola Omotosho; Kolawole Sodeinde; Olufunmilola Abolurin; Adesola Adekoya; Olumide Abiodun (Heliyon, 2022)
Background: Neonatal death rates are high in sub-Saharan Africa and the majority of these deaths are preventable. Antenatal care (ANC) is a good channel for the reduction of neonatal deaths. This study aimed to assess newborn care practices among lactating women in Nigeria and determine their relationship with ANC attendance. Methodology: This was a cross-sectional survey involving 241 lactating mothers selected using the cluster sampling method. A structured interviewer-administered questionnaire was employed to obtain data. The Chi-square test was used to assess the associations between categorical variables. Logistic regression was used to determine the predictors of umbilical cord care, thermal care, and neonatal vaccination status. Good cord care was defined as having minimum of three appropriate practices concerning the use of clean instruments to tie the cord, use of clean instruments to cut the cord, and application of chlorhexidine, 70% alcohol, saltwater, or nothing on the cord), Results were presented as odds ratios (ORs). P < 0.05 was taken as statistically significant. Results: The mean age of participants was 29.0 ± 5.5 years. Most participants reported that sterile instruments were used to cut their baby's umbilical cords; that their babies were dried immediately after placenta delivery and that their babies were fully vaccinated (91.0%, 90.5%, and 85.1% respectively). ANC visits (aOR = 8.0, p = 0.02) and place of delivery (aOR = 10.6, p = 0.01) were significantly associated with good umbilical cord care practices. However, none of the participants' sociodemographic characteristics were significantly associated with newborn thermal care and vaccination status. Conclusion: The prevailing antenatal care services are ineffective in preparing mothers for newborn care. Place and frequency of ANC have positive associations with umbilical cord care. There is a need to implement quality ANC that will enhance maternal and neonatal outcomes and implement innovative interventions to enhance ANC attendance. The WHO positive pregnancy experience model should be implemented.